2015
DOI: 10.1586/14737167.2016.1102635
|View full text |Cite
|
Sign up to set email alerts
|

Condom effectiveness in reducing heterosexual HIV transmission: a systematic review and meta-analysis of studies on HIV serodiscordant couples

Abstract: Though imperfect, condoms reduce HIV transmission by more than 70% when used consistently by HIV serodiscordant heterosexual couples. Social, cultural and biological differences need to be studied further to inform projection modelers and policy makers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 61 publications
0
52
0
1
Order By: Relevance
“…Right after HIV discovery, condom effectiveness in reducing the HIV risk was evaluated (Conant, Hardy, Sernatinger, Spicer, & Levy, 1986;Davis & Weller, 1999;Judson, Ehret, Bodin, Levin, & Rietmeijer,1989;Pinkerton & Abramson, 1997;Rietmeijer, Krebs, Feorino, & Judson,1988;Van de Perre, Jacobs, & Sprecher-Goldberger, 1987). Regarding heterosexual transmission, a 60%-96% relative risk reduction has been estimated (Giannou et al, 2015;Lassi, Imam, Dean, & Bhutta, 2014;Liu et al, 2014;UNAIDS, 2004;Weller & Davis, 2002). A meta-analysis carried out by Giannou et al, 2015 evaluated HIV infection RRs after comparing "always" versus "never", and "always" versus "not always" use and estimated that, consistent use provide an approximately 70% relative reduction in HIV risk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Right after HIV discovery, condom effectiveness in reducing the HIV risk was evaluated (Conant, Hardy, Sernatinger, Spicer, & Levy, 1986;Davis & Weller, 1999;Judson, Ehret, Bodin, Levin, & Rietmeijer,1989;Pinkerton & Abramson, 1997;Rietmeijer, Krebs, Feorino, & Judson,1988;Van de Perre, Jacobs, & Sprecher-Goldberger, 1987). Regarding heterosexual transmission, a 60%-96% relative risk reduction has been estimated (Giannou et al, 2015;Lassi, Imam, Dean, & Bhutta, 2014;Liu et al, 2014;UNAIDS, 2004;Weller & Davis, 2002). A meta-analysis carried out by Giannou et al, 2015 evaluated HIV infection RRs after comparing "always" versus "never", and "always" versus "not always" use and estimated that, consistent use provide an approximately 70% relative reduction in HIV risk.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding heterosexual transmission, a 60%-96% relative risk reduction has been estimated (Giannou et al, 2015;Lassi, Imam, Dean, & Bhutta, 2014;Liu et al, 2014;UNAIDS, 2004;Weller & Davis, 2002). A meta-analysis carried out by Giannou et al, 2015 evaluated HIV infection RRs after comparing "always" versus "never", and "always" versus "not always" use and estimated that, consistent use provide an approximately 70% relative reduction in HIV risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere, Holmes et al reported lower levels of knowledge about condom use among Nigerian soldiers (13). Despite the effectiveness of condoms in significantly reducing HIV transmission (1,14), its use remains distressingly sub-optimal in a high risk group such as the military personnel (3,5,12,15,16). The current study mainly aimed at investigating the patterns and determinants of the use of male condoms among a representative sample of Cameroonian soldiers.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that new advances in medical treatments, such as pre-exposure prophylaxis (PrEP), will help facilitate the prevention of onwards transmission of HIV. However, the practicing of HIV disclosure and safe sex remain fundamental to HIV prevention efforts (Giannou et al, 2015; O'Connell, Reed & Serovich, 2015).…”
Section: Introductionmentioning
confidence: 99%